Low-voltage ride-through capability improvement in autonomous AC microgrids: A review of existing control approaches - Dehghani Arani, Zahra; Taher, Seyed Abbas; Guerrero, Josep M. (Renewable & sustainable energy reviews, 2025)
In autonomous AC microgrids under short-circuit fault or overload conditions, the semiconductor switches of grid-forming inverter-based distributed energy resources are subject to serious damage due to the overcurrent issue caused by these low-voltage phenomena. Limiting the current of the grid-forming inverter at the primary level control structure and as a result, improving the low-voltage ride-through capability of the isolated microgrid is more desirable than using hardware protection equipment. The current limiting capability has been implemented for single-loop control structure to protect the inverter under overload conditions. The existing methods for limiting the current of grid-forming inverter during fault conditions, which are often implemented by considering two inner loops of current and voltage control, can be considered in three general categories: 1) limiting the reference current derived from the voltage controller, 2) changing the reference voltage obtained from the power-sharing loop by utilizing the concept of virtual impedance, and 3) changing the inverter's control structure. In fact, besides the current limiting strategy, other parts of the multi-loop control system could be efficient in the low-voltage ride-through operation. The effects of the reference frame of the control system for the independent control of the phases, the power-sharing method in autonomous microgrids including three-phase and single-phase grid-forming inverter-based distributed energy resources, and preventing voltage distortion when restricting the inverter current under voltage drop conditions are critical issues that are discussed in the literature review presented in this paper. [Display omitted] •Single-loop and multi-loop control for LVRT of grid-forming inverters are reviewed.•LVRT in autonomous AC microgrids is realized by limiting the inverter current.•Preventing voltage distortion should be considered in the current limiting method.•Power-sharing method is effective in presence of three- and single-phase resources.